IMPLEMENTASI LITERASI KEUANGAN SYARIAH PADA ALOKASI DANA ZISWAF MASYARAKAT - ANNA SARDIANA; ZULFISON ZULFISON (Universitas Islam Negeri Imam Bonjol Padang, 2018)
One pattern of welfare equality can be done through the distribution of wealth that allocated from the assets of individuals who have adequate economic ability through the distribution of Zakat, Infaq, Shadaqah and Endowments (ZISWAF). Islamic financial literacy in this study measures the level of knowledge, abilities and attitudes of individuals in their decision to allocate funds to the ZISWAF. This research is limited to people who allocate their ZISWAF funds through the Dompet Dhuafa Amil Zakat Institution and LAZ Al-Azhar. The method used is descriptive with a quantitative approach. Data collection done by using questionnaires, interviews and observations and indepth interviews. The results of this study indicate that there is an influence of Islamic financial literacy on the allocation of public funds to Ziswaf.